Bibliometric Analysis of the Optimization of Goods and Services Procurement Administration through E-Purchasing Implementation in the Public Sector - Indrianti, Tata Tiara Dwi (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2025)
This study conducts a bibliometric analysis to explore the development of the application of e-purchasing in the procurement of goods and services in the public sector in Indonesia during the period 2019 to 2024. By utilizing data derived from the Google Scholar database with Publish or Perish (PoP) and VOSViewer software, the authors found that the number of scientific publications related to e-purchasing has increased significantly each year, with a total of 537 articles identified. In addition, this study identified several barriers to e-purchasing implementation, including limited Human Resources and resistance to work culture change. The analysis also shows the existence of four main clusters in this research, as well as changes in terms used in publications from year to year. Keywords: procurement, e-purchasing and public sector